PENERAPAN PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA MATERI ENERGI BUNYI (Penelitian Tindakan Kelas Pada Siswa Kelas IV Sekolah Dasar Negeri 1 Kaliwadas Kecamatan Sumber Kabupaten Cirebon) - Putri, Dea Yantono; Jayadinata, Asep Kurnia; Subarjah, Herman (Jurnal Pena Ilmiah, 2017)
Based on preliminary observation in VIth grader students SDN 1 Kaliwadas obtained a problem, namely teacher centered learning.The teacher in the learning method using lectures and assignments so that students quickly feel bored in following the learning. This resulted in low students learning outcomes. Based on these conditions applied inquiry learning in order to overcome the problem. because inkuiry learning emphasizes students to seek and find their own answers to problems or in other words student centered learning. This research uses classroom action rresearch with research design referring to Kemmis and Taggart. The research process is carried out for three cycles. The research that has been done can be concluded that the application of inkuiry learning can improve student learning outcomes on sound energy materials. It is proven that the target of learning achievement that is 85% of all students reach KKM, 91% of students expressed on the learning.